Comparative Study of Gastrointestinal Parasites of Free Ranged and Caged Chickens in Lokoja, Kogi State - J. S. , Ngwama; V. O. , Kayode; A., Mathias; W. , Yanusa; Y. D. , Dakum (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Poultry Production plays an important role in the provision of animal protein to the timing Nigeria population and other domestic Animals. It is also vital to the nation’s economy as a source of income to poultry farmers and revenue to the entire nation. Rearing of chicken on a large scale is greatly affected by parasitic diseases and their effects cause difficulties in poultry management, which may affect the productivity rate, growth rate, sometime may even lead to total extermination of the entire poultry. Helminths are important parasites of poultry production that may lead low productivity. The aim of this study was to compare the prevalence and intensity of infection of helminths in free ranged and caged chicken slaughtered in the study area. A total of 150 faecal samples were collected from the intestinal tract of slaughtered chickens in the study area were examined using sedmentation and floatation methods for the presence of adult worm, segments, ova or eggs of gastrointestinal parasites. Samples of chickens examined in the study area were found to be positive with two species from class nematoda (Ascaridia galli and Heterakis gallinarum). The gastrointestinal cestodes identified were Choanotaenia infundibulum, Raillietina echinobothrida and Capillaria species, while the pparasites of chicken in the study area, with 49(65 .33%) of the local chicken and 19(25.33%) of the caged system chicken examined found to be infected with it. Ascaridia galli proved to be the second most prevalent species, with an infection rate of 31(41.33%) and 14(18.67%) for free range and caged chickens. All the 75 local chickens examined, were found to be infected with one or more gastrointestinal parasites 75 (100%). The high gastrointestinal parasites observed in the study area have a strong relationship with their mode of feeding and the birds’ living conditions. This high prevalence may be responsible for reduced body weight, reduction in egg production and deaths of some or complete extermination of the whole poultry.